Non-Puerperal Uterin Inversion Caused by Myoma of the Uterus - (:unkn) unknown (My University, 2016)
0

Non puerperal uterine inversion is a rare event and mostly caused by uterine myomas. Herein a case ofuterine inversion caused by myoma protruding through vagina is presented. Uterine inversion should beconsidered in patients with uterine mass protruding to vagina.
Keywords: Kadın Hastalıkları ve Doğum